Posyandu's Contribution to Reducing Stunting Prevalence in the Community - Sari, Indah Permata; Rodiyah, Isnaini (Indonesian Journal of Cultural and Community Development, 2024)
The general background stunting is a health problem that can reduce the quality of human resources, and the role of posyandu is very important in its management. Specific background this research focuses on Wunut Village in Porong District, where the prevalence of stunting is a major concern. Knowledge Gap: Although many studies on stunting exist, the specific role of posyandu in the local context has been less explored. Aims this study to analyze the role of posyandu in reducing the prevalence of stunting in Wunut Village. Results this study posyandu as a motivator, facilitator, and mobilizer in increasing community awareness and access to health services related to stunting. Posyandu has successfully invited the community to actively participate in health activities and provided services such as growth monitoring and distribution of nutritional supplements. Novelty this research highlights the tangible contributions of posyandu in the local context, providing new insights into community-based approaches to addressing stunting. Implications these findings indicate the importance of strengthening posyandu as a health institution in stunting reduction efforts and the need for continuous support from the government and community to enhance the effectiveness of health programs. Highlights: Posyandu serves as a motivator, encouraging community participation in health activities. Facilitates access to basic health services and nutritional support for mothers and children. Highlights the importance of community-based approaches in addressing stunting issues. Keywords: Posyandu, Stunting, Community Health, Nutritional Support, Health Services